2014
DOI: 10.1614/ws-d-13-00041.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Germination of Citronmelon (Citrullus lanatusvar.citroides)

Abstract: Citron melon is a monoecious, hairy annual vine commonly found in citrus orchards, and cotton and peanut fields. Information is not available on the effect of various environmental factors on the germination of citron melon. Laboratory and greenhouse experiments were carried out in 2011 and 2012 to determine the effect of light, temperature, salinity, pH, simulated water stress, and depth of sowing on the germination of citron melon. Citron melon germination was affected by various environmental factors. Highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…Sugar Baby [ 34 ], and C. lanatus var. citroides [ 35 ]. In addition, seed germination of other species of Cucurbitaceae is sensitive to the germination temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar Baby [ 34 ], and C. lanatus var. citroides [ 35 ]. In addition, seed germination of other species of Cucurbitaceae is sensitive to the germination temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration required for 50% inhibition of maximum germination was 70.6 mM NaCl ( Figure 6A). The maximum concentration at which no seed could germinate for barnyardgrass (Echinochloa crus-galli) (Sadeghloo et al, 2013), citronmelon (Ramirez et al, 2014), Japanese brome (Li et al, 2015), muskweed (Honarmand et al, 2016), and spotted spurge (Asgarpour et al, 2015) was 400, 300, 360, 250, and 160 mM NaCl, respectively. These results showed that velvetleaf is not tolerant to salinity as compared with the above weed species, which could germinate at high NaCl concentration.…”
Section: Effect Of Salinity and Alkalinity Stressmentioning
confidence: 99%
“…In many cases, when dormancy level is sufficiently low, seeds lose their requirement of alternating temperatures and/or light to germinate and can germinate under a wide range of constant temperatures (Benech‐Arnold et al ., ). Knowledge about the way in which the environment modulates dormancy alleviation in weed species is useful to predict germination and seedling emergence patterns in the field, and to develop rational strategies of weed management (Ramirez et al ., ). Up to now, factors affecting dormancy alleviation of C. cardunculus achenes have not been assessed.…”
Section: Introductionmentioning
confidence: 97%